A new genus and five new species of Eriophyoidea (Prostigmata) associated with palm trees from Brazilian Amazon - Navia, Denise; Flechtmann, Carlos H.w. (Zootaxa, 2005)
A new genus and five new species of eriophyoid mites associated with native palm trees (Arecaceae) are described from Brazilian Amazon. The new genus and two new species are in the family Eriophyidae: Euterpia fissa n. gen. & n. sp. from Euterpe precatoria and Notostrix spinula n. sp. from Mauritia flexuosa. Three new species belong to the family Phytoptidae: Palmiphytoptus barbosae n. sp. from Astrocaryum acaule; Propilus alternatus n. sp. from Mauritia flexuosa and Propilus tavaresi n. sp. from Elaeis oleifera.